Diagnostic strategy of metagenomic next-generation sequencing for gram negative bacteria in respiratory infections - Wenyan Liang; Qun Zhang; Qian Qian; Mingyue Wang; Yuchen Ding; Ji Zhou; Yi Zhu; Yu Jin; Xuesong Chen; Hui Kong; Wei Song; Xin Lu; et al. (Annals of Clinical Microbiology and Antimicrobials, 2024)
Abstract Objective This study aims to identify the most effective diagnostic method for distinguishing pathogenic and non-pathogenic Gram-negative bacteria (GNB) in suspected pneumonia cases using metagenomic next-generation sequencing (mNGS) on bronchoalveolar lavage fluid (BALF) samples. Methods The effectiveness of mNGS was assessed on BALF samples collected from 583 patients, and the results were compared with those from microbiological culture and final clinical diagnosis. Three interpretational approaches were evaluated for diagnostic accuracy. Results mNGS outperformed culture significantly. Among the interpretational approaches, Clinical Interpretation (CI) demonstrated the best diagnostic performance with a sensitivity of 87.3%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 98.3%. CI’s specificity was significantly higher than Simple Interpretation (SI) at 37.9%. Additionally, CI excluded some microorganisms identified as putative pathogens by SI, including Haemophilus parainfluenzae, Haemophilus parahaemolyticus, and Klebsiella aerogenes. Conclusion Proper interpretation of mNGS data is crucial for accurately diagnosing respiratory infections caused by GNB. CI is recommended for this purpose.